Type material of helminthes in the Museo de Historia Natural, Universidad Nacional Mayor de San Marcos, (MUSM), Lima, Peru - Morales, Elizabeth (2005)
A list of 44 species of 511 type specimens (34 holotypes, 9 allotypes, 418 paratypes, and 50 syntypes) of helminthes (Trematoda, Monogenea, Cestoidea, Nematoda and Acanthocephala), parasitic in vertebrates and invertebrates from Peru, Chile and the United States of America, and preserved in the Helminthological Collections of the Museo de Historia Natural, Universidad Nacional Mayor de San Marcos (MUSM), Lima, Peru, is presented herein. Some nomenclatural comments are also included.